Low serum dehydroepiandrosterone examined by liquid chromatography‐tandem mass spectrometry correlates with poor prognosis in hormone‐naïve prostate cancer. Issue 4 (30th November 2015) - Miyoshi, Yasuhide; Uemura, Hiroji; Umemoto, Susumu; Sakamaki, Kentaro; Taguri, Masataka; Suzuki, Kazuhiro; Shibata, Yasuhiro; Masumori, Naoya; Ichikawa, Tomohiko; Mizokami, Atsushi; Sugimura, Yoshiki; Nonomura, Norio; et al.
Abstract : BACKGROUND: There is no consensus on blood adrenal androgen concentrations in men with different stages and pathological grades of prostate cancer. In this study, dehydroepiandrosterone (DHEA) concentrations in blood were examined by ultrasensitive liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). We analyzed the correlation between DHEA concentrations in blood and clinicopathological findings of prostate cancer. METHODS: We analyzed 196 men (mean age 70 years) with prostate cancer. The patients underwent systematic needle biopsy, and peripheral blood sampling was conducted for measurement of DHEA. DHEA concentrations in blood were determined using LC‐MS/MS method. Patient age, serum prostate‐specific antigen, prostate volume measured by ultrasound, and DHEA levels in blood were compared with Gleason score and clinical stage by multivariate analyses. RESULTS: Median value of PSA and prostate volume were 11.5 ng/ml and 27.7 ml, respectively. Median concentration of DHEA in blood was 1, 506.4 pg/ml. There was no correlation between serum DHEA and clinical variables such as age, serum PSA, and prostate volume. In multivariate analysis, low serum DHEA levels in prostate cancer patients were significantly related to high Gleason score and advanced clinical stage. Serum PSA levels in prostate cancer patients were also significantly associated with high Gleason score and advanced clinical stage. High serum PSA and low serum DHEA levels were significantly associated with poor prognosis factors in men with hormone‐naïve prostate cancer. CONCLUSIONS: DHEA concentrations in blood were examined by newly developed ultrasensitive LC‐MS/MS. We confirmed that low serum DHEA levels in prostate cancer patients were related to high Gleason score and advanced clinical stage. These results suggest that serum DHEA level may be a useful prognostic factor in prostate cancer patients. Prostate 76:376–382, 2016 . © 2015 Wiley Periodicals, Inc.